Gaming the system designing with Gamestar mechanic - Tekinba, Katie Salen; Gresalfi, Melissa 1977-; Peppler, Kylie A.; Santo, Rafi 1982- (The John D. and Catherine T.Macarthur Foundation series on digital media and learning, 2014)
Understanding games as systems, with complex interactions of game elements and rules